2014
DOI: 10.1136/bjsports-2014-093574
|View full text |Cite
|
Sign up to set email alerts
|

Objectively measured physical activity trajectories predict adolescent bone strength: Iowa Bone Development Study

Abstract: Background Physical activity improves bone strength and reduces the risk for osteoporotic fractures. However, there are substantial gaps in our knowledge as to when, how and how much activity is optimal for bone health. Purpose In this cohort study, we examined developmental trajectories of objectively measured physical activity from childhood to adolescence to discern if moderate-and-vigorous intensity physical activity (MVPA) predicts bone strength. Methods Starting at age 5 and continuing at 8, 11, 13, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
111
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(115 citation statements)
references
References 18 publications
4
111
0
Order By: Relevance
“…The Iowa Bone Development Study (a prospective cohort study) showed 10% to 16% greater hip BMC and 8% greater hip areal BMD in participants who accumulated the greatest amount of activity from childhood through adolescence (12-year follow-up). 39 For patients with limited mobility, reducing immobility through physical therapy 40 or the use of vibrating platforms can be helpful. 29,41 Reducing inflammation, undernutrition, or hormone imbalances also is necessary.…”
Section: Therapy For Childhood Skeletal Fragilitymentioning
confidence: 99%
“…The Iowa Bone Development Study (a prospective cohort study) showed 10% to 16% greater hip BMC and 8% greater hip areal BMD in participants who accumulated the greatest amount of activity from childhood through adolescence (12-year follow-up). 39 For patients with limited mobility, reducing immobility through physical therapy 40 or the use of vibrating platforms can be helpful. 29,41 Reducing inflammation, undernutrition, or hormone imbalances also is necessary.…”
Section: Therapy For Childhood Skeletal Fragilitymentioning
confidence: 99%
“…Demographic characteristics of the IBDS subject population include being 95% white, with two-thirds of the subjects' parents having college degrees (Janz et al, 2014;Janz et al, 2015). This secondary analysis focuses on IBDS participants with assessments in early adulthood, specifically 18 to 22 year old males (n = 136, mean age 19.7±0.7 years) and females (n = 167, mean age 19.7±0.6 years).…”
Section: Participant Recruitment and Study Designmentioning
confidence: 99%
“…Participants for the IBDS were recruited from 1998 to 2001, when subjects were approximately 5 years of age, from a larger group of Midwestern children (n = 890) that had been recruited and were already participating in the Iowa Fluoride Study (Janz et al, 2014;Janz et al, 2015). Original recruitment for the Iowa Fluoride Study occurred in eight Iowa hospitals from 1992 to 1995 immediately following birth.…”
Section: Participant Recruitment and Study Designmentioning
confidence: 99%
See 2 more Smart Citations